Insights into the Melipona scutellaris (Hymenoptera, Apidae, Meliponini) fat body transcriptome - Cristina Soares de Sousa; José Eduardo Serrão; Ana Maria Bonetti; Isabel Marques Rodrigues Amaral; Warwick Estevam Kerr; Andréa Queiroz Maranhão; Carlos Ueira-Vieira (Genetics and Molecular Biology, 2013)
The insect fat body is a multifunctional organ analogous to the vertebrate liver. The fat body is involved in the metabolism of juvenile hormone, regulation of environmental stress, production of immunity regulator-like proteins in cells and protein storage. However, very little is known about the molecular mechanisms involved in fat body physiology in stingless bees. In this study, we analyzed the transcriptome of the fat body from the stingless bee Melipona scutellaris. In silico analysis of a set of cDNA library sequences yielded 1728 expressed sequence tags (ESTs) and 997 high-quality sequences that were assembled into 29 contigs and 117 singlets. The BLAST X tool showed that 86% of the ESTs shared similarity with Apis mellifera (honeybee) genes. The M. scutellaris fat body ESTs encoded proteins with roles in numerous physiological processes, including anti-oxidation, phosphorylation, metabolism, detoxification, transmembrane transport, intracellular transport, cell proliferation, protein hydrolysis and protein synthesis. This is the first report to describe a transcriptomic analysis of specific organs of M. scutellaris. Our findings provide new insights into the physiological role of the fat body in stingless bees.